Small business : critical perspectives on business and management. Volume II (New York : Routledge, 2000)
This volume presents Critical Perspectives on Business and Management of Small Business about: Growth; Employment and Job Generation; and Finance.
Keywords: Business; Enterprises; Entrepreneurship; Small business; Entrepreneurship; Small business; New business enterprises; Self-employed.